The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1099/00221287-139-12-3157
|View full text |Cite
|
Sign up to set email alerts
|

Response of intracellular carbohydrates to a NaCl shock in Rhizobium leguminosarum biovar trifolii TA-1 and Rhizobium meliloti SU-47

Abstract: ~ ~The dynamic response of cellular carbohydrates to a NaCl shock in Rhizobium leguminosarum biovar trifolii TA-1 (0.25 M-NaCI) and Rhizobium meliloti SU-47 (0.4 M-NaCl) grown in NaC1-free medium was investigated in nongrowing cell cultures and in cell suspensions, using in vivo NMR. After transferring cells grown in a NaC1-free medium to a glutamic-acid-free medium containing mannitol and NaCI, both strains immediately responded to the increased osmotic pressure by augmenting the cellular trehalose content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
2
33
1
Order By: Relevance
“…The results from this current study showed that increasing the osmotic pressure of the growth medium increases trehalose accumulation in rhizobia which supports previously published reports that rhizobia accumulate trehalose in response to osmotic stress (Breedveld et al, 1991;Breedveld et al, 1993;Streeter, 2003;Streeter, 2007).…”
Section: General Discussion and Conclusionsupporting
confidence: 80%
See 2 more Smart Citations
“…The results from this current study showed that increasing the osmotic pressure of the growth medium increases trehalose accumulation in rhizobia which supports previously published reports that rhizobia accumulate trehalose in response to osmotic stress (Breedveld et al, 1991;Breedveld et al, 1993;Streeter, 2003;Streeter, 2007).…”
Section: General Discussion and Conclusionsupporting
confidence: 80%
“…Rhizobia synthesise endogenous trehalose when grown in a hyperosmotic environment to compensate for the difference in osmotic pressure across the cytoplasmic membrane (Streeter, 1985;Breedveld et al, 1993). There were no statistically significant differences in the trehalose content in this study, however the trehalose content was higher in TA1 cells grown in the peat extract compared to the control and was unaffected by fractionation of the peat extract.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Under nonstress conditions, S. meliloti can take up trehalose and use it as its sole carbon and energy source (17). Under various stress conditions, S. meliloti synthesizes and accumulates trehalose, which can serve as a compatible solute (7,22). In cultures grown at high osmolarity, exogenous trehalose stimulates the accumulation of intracellular trehalose (43); this has been found to decrease the generation time (18).…”
mentioning
confidence: 99%
“…This has been suggested previously in studies where the growth rate of rhizobia was restricted in low-wateractivity medium and enhanced desiccation tolerance was attrib- uted to adaptation to osmotic and other stresses during growth (10,28). Rhizobia synthesize endogenous trehalose when grown in a hyperosmotic environment to compensate for the difference in osmotic pressure across the cytoplasmic membrane (23,29). In this study, while there were no statistically significant differences, the trehalose content in TA1 was higher in cells grown in the peat extract than in the control and was unaffected by fractionation of the peat extract.…”
Section: Discussionmentioning
confidence: 35%